2018
DOI: 10.1021/acs.biomac.8b00293
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Temperature-Sensitive and Chemically Cross-Linked Poly(N-isopropylacrylamide)/Photosensitizer Hydrogels for Applications in Photodynamic Therapy

Abstract: A novel poly( N-isopropylacrylamide) (PNIPAM) hydrogel containing different photosensitizers (protoporphyrin IX (PpIX), pheophorbide a (Pba), and protoporphyrin IX dimethyl ester (PpIX-DME)) has been synthesized with a significant improvement in water solubility and potential for PDT applications compared to the individual photosensitizers (PSs). Conjugation of PpIX, Pba, and PpIX-DME to the poly( N-isopropylacrylamide) chain was achieved using the dispersion polymerization method. This study describes how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…Value of T 0 can be shifted to 34-42 °C by copolymerization of NIPAM with more hydrophilic monomers, e.g. acrylamide (AA) [30]. In the developed NPs, shell is of poly(NIPAM-co-AA) copolymer, which makes NPs thermoresponsive.…”
Section: Resultsmentioning
confidence: 99%
“…Value of T 0 can be shifted to 34-42 °C by copolymerization of NIPAM with more hydrophilic monomers, e.g. acrylamide (AA) [30]. In the developed NPs, shell is of poly(NIPAM-co-AA) copolymer, which makes NPs thermoresponsive.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, incorporation into hydrogels did not affect the efficiency of ROS production, which makes them promising candidates as drug delivery platforms for PS. 185 Furthermore, Zampini et al studied hydrogels with incorporated silica-PPIX samples in the presence of gold nanoparticles. This preliminary study showed enhanced ROS production and an improved excitation field due to plasmonic effect.…”
Section: Porphyrins Haematoporphyrinmentioning
confidence: 99%
“…This indicated uptake by the cells via folate-receptor Pheo a was also covalently linked to the hydrogel matrix of PNIPAM to yield a stable and water soluble nanohydrogel formulation. 185 This nanoporous 3D structure prevented the aggregation of the PS and enhanced the efficiency of singlet oxygen production. The photosensitizer also displayed an excellent in vitro PDT efficacy wherein Pheo a-PNIPAM formulation gave a LD 90 of 9 × 10 -5 as compared to Pheo a alone, which displayed a LD 90 of 5 × 10 -7 (HT-29 cancer cells).…”
Section: Chlorinsmentioning
confidence: 99%
“…[ 18 ] Light‐irradiation responsive hydrogels also showed great PDT success. [ 19 ] Our group developed a new cationic chalcogenoviologens‐loaded WD, which exhibited a significant photodynamic antibacterial effect and the ability to promote skin regeneration. [ 20 ] However, such WD cannot provide convenient treatment under electrical stimulation at the same time.…”
Section: Introductionmentioning
confidence: 99%